QUALITATIVE STUDY OF IUD CONTRACEPTION SELECTION IN COUPLES OF REPRODUCTIVE AGE IN TUBBI TARAMANU HEALTH CENTER - Putri Dwi Sundari; Lujnah Lujnah; Andi Alim; Asriani Minarti S (Indonesian Journal for Health Sciences, 2023)
Intrauterine Device (IUD) is a contraceptive device in the uterus, The IUD works by inhibiting the movement of sperm into the uterine canal to prevent pregnancy from occurring. This study aims to find out in-depth about the choice of IUD contraception for couples of childbearing age at the Tubbi Taramanu Health Center, Polewali Mandar Regency, West Sulawesi Province. This research method is qualitative research with a total of 7 informants. The results of this study were that the informants' knowledge regarding the IUD contraceptive device was sufficient to know and understand so the informant chose the IUD contraceptive device to use. There are complaints that the husband feels during intercourse after using the IUD, but these complaints are temporary so the husband continues to support him in choosing and using the IUD contraceptive because it is considered more effective and efficient than other contraceptives. There were side effects felt by the informants after using the IUD but these side effects were felt to be harmless because they could be taken by taking blood-boosting vitamins/supplements. This research suggests that to increase public knowledge and understanding about IUD contraception, it is hoped that health workers will conduct counseling directly in people's homes. It is suggested to acceptor husbands not only to provide moral support to mothers but support in the form of attention if side effects occur after using IUD contraception.